Time-Resolved Analysis of Left Ventricular Shear Wave Amplitudes in Cardiac Elastography for the Diagnosis of Diastolic Dysfunction - Elgeti, Thomas; Steffen, Ingo G.; Knebel, Fabian; Haettasch, Robert; Hamm, Bernd; Braun, Juergen; Sack, Ingolf (Investigative Radiology, 2016)
Objectives The aim of this study was to investigate the diagnostic potential of changes in left ventricular (LV) shear wave amplitudes (SWAs) over the cardiac cycle measured by cardiac magnetic resonance elastography. Materials and Methods Electrocardiography-triggered SWA-based cardiac magnetic resonance elastography with 24.13-Hz external vibration frequency was performed in asymptomatic young (n = 10) and old (n = 10) subjects and patients (n = 30) with echocardiographically proven mild, moderate, or severe diastolic dysfunction. The temporal delay between change in SWA and morphological change in the LV wall, that is, time of isovolumetric elasticity relaxation normalized against heart rate, was calculated for diastole (τR 0). Diastolic levels of LV SWA were calculated and normalized against SWA in the chest wall (U 0 [dia]). Nonparametric testing was used for statistical evaluation. Accuracy of the parameters was investigated using receiver operating characteristic analysis against echocardiography. Interobserver and intraobserver variability for the temporal delay between change in SWA and morphological changes was tested according to Bland and Altman. Results Young and old control subjects showed median (standard error of mean, interquartile range) τR 0 of 99 (5, 93-103) and 82 (7, 66-95). In patients with diastolic dysfunction, τR 0 was 131 (20, 107-171), 158 (14, 108-172), and 138 (14, 107-174) with statistically significant differences between old subjects and patients with diastolic dysfunction (P = 0.01).U 0 (dia) was 0.94 (0.05, 0.86-1.04) and 0.71 (0.06, 0.61-0.92) in young and old controls, respectively (P = 0.063). Compared with young subjects, patients with mild, moderate, and severe diastolic dysfunction displayed significantly reduced U 0 (dia) of 0.69 (0.06, 0.53-0.82), 0.56 (0.04, 0.46-0.64), and 0.48 (0.04, 0.43-0.61) (P < 0.001).τR 0 /U 0 (dia) cutoff values for prediction of diastolic dysfunction were 107/0.66, corresponding to the area under the receiver operating characteristic values of 0.84/0.87 with 74%/74% sensitivity and 85%/85% specificity. Interobserver and intraobserver variability ranged from -0.05 to 0.05 with 95% agreement. Conclusions In diastolic dysfunction, low-frequency SWAs show distinct changes in the normalized time of isovolumetric elasticity relaxation for the LV (τR 0) and the diastolic level of SWA (U 0 [dia]). Both parameters have good diagnostic performance for diagnosis of diastolic dysfunction.
CRIS-Team Scopus Importer:2022-08-03
Keywords: cardiac time intervals; diastolic dysfunction; heart; magnetic resonance elastography